Misorientations in [001] magnetite thin films studied by electron backscatter diffraction and magnetic force microscopy - SHVETS, IGOR; MURPHY, SHANE (AMERICAN INSTITUTE OF PHYSICS, 2007)
Magnetite thin films grown on 001 oriented MgO substrates are analyzed by means of electron backscatter diffraction EBSD analysis and magnetic force microscopy in applied fields. The EBSD technique enables the crystallographic orientation of individual grains to be determined with a high spatial resolution up to 20 nm on such ceramic samples. A high image quality of the recorded Kikuchi patterns was achieved enabling multiphase scans and high spatial resolution measurements. Upon annealing in air, the magnetic properties of the magnetite thin films were found to change considerably. Using the EBSD analysis, we find that misoriented grains remaining after the annealing step form small islands with a size of about 100 nm. The size and distribution of these islands correspond well to the observations of antiferromagnetic pinning centers within the magnetic domain structures carried out by magnetic force microscopy on the same samples.
Journal of Applied Physics
PROCEEDINGS OF THE TENTH JOINT MMM/INTERMAG CONFERENCE
PUBLISHED
Keywords: Atomic, molecular and chemical physics; thin films